2018
DOI: 10.1002/pts.2415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of active films incorporated with montmorillonite clay and α‐tocopherol: Potential of nanoparticle migration and reduction of lipid oxidation in salmon

Abstract: Fat‐rich fish such as salmon are highly susceptible to lipid oxidation, which affects the quality of the product. The compound α‐tocopherol is widely used as an antioxidant added directly to food or through the incorporation in active packaging besides having activity of vitamin E, which is an essential nutrient to the human body absorbed from food. The objective of this paper was to evaluate the montmorillonite (MMT15A) and α‐tocopherol migration potential and antioxidant effect of chitosan/MMT15A/α‐tocophero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 41 publications
(76 reference statements)
0
12
0
Order By: Relevance
“…During the experimentation process, it was found in the intial process of starting it was getting softer as they were in contact with water and gradually its reduced as the films were absorbing more moisture. The significant influence of combiantion ratios was observed for swelling index of the films [28].…”
Section: Swelling Of Filmsmentioning
confidence: 90%
“…During the experimentation process, it was found in the intial process of starting it was getting softer as they were in contact with water and gradually its reduced as the films were absorbing more moisture. The significant influence of combiantion ratios was observed for swelling index of the films [28].…”
Section: Swelling Of Filmsmentioning
confidence: 90%
“…A full factorial experimental design was performed according to previous studies (Dias et al, 2014; Dias et al, 2019), considering the MMT15A (0; and 1 g·100 g −1 ) and tocopherol (0; 5; 10; and 20 g·100 g −1 ) concentrations as factors (Table 1). The experiment was performed using a completely randomized design with three replications.…”
Section: Methodsmentioning
confidence: 99%
“…Nano-or microencapsulation can be carried out using different carriers to incorporate the active additives. Dias et al [12] demonstrated the antioxidant capacity and the controlled release of α-tocopherol incorporated to montmorillonite by using PCL as the polymer matrix. Sogut et al [8] used chitosan and PCL-based films containing nanocellulose (2% w/w) and grape seed extract to obtain bilayer films for transferring functional polyphenolic compounds in food packaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…Among various natural active additives, α-tocopherol (TOC) is known to be a potent antioxidant agent and films loaded with this antioxidant have been proved to be effective in retarding lipid oxidation [19][20][21]. This natural additive is authorized as food contact material by EFSA and FDA authorities [22], and it can provide antioxidant/antimicrobial properties to the food product while also stabilizing the polymer matrix during processing [12]. The incorporation of α-tocopherol into different biopolymers, in particular poly(lactic acid) (PLA) [23][24][25][26] and edible polymers such as methylcellulose [27] or chitosan [19], has been reported.…”
Section: Introductionmentioning
confidence: 99%